KUALITAS HADIS TENTANG WARISAN BERBEDA AGAMA - Nurlaila Nurlaila (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
Hadith scholars agree that the elements that must be met by a qualified matan shahih there are two kinds, namely avoid syudzuz (irregularities) and avoid 'illat (disabled). That is, two elements must be the primary reference for researching matan hadith. Matan benchmark research proposed by scholars is not uniform. Saladin al-Adlabi concluded that the benchmark for the study of honor there are four, namely: 1. It is not contrary to the instructions of the Koran; 2. Does not conflict with stronger traditions; 3. contrary to common sense, sense and history; 4. The composition of statement shows the characteristics of the prophetic word.